Social-Climbing Projects of Families in the Context of Human Trafficking from Nigeria to France - Apard, Élodie; Diagboya, Precious; Simoni, Vanessa (Anti-Trafficking Review, 2025)
Most African women involved in prostitution in major European cities today come from Edo State in Nigeria, where human trafficking has become an economic model. Despite moral judgment and the stigmatisation of sex workers in Nigeria, sending a woman to Europe represents an opportunity that many families decide to take as they rely on the potential financial benefits that would allow collective social climbing. This article analyses migration for prostitution purposes as a family project, helping to shed light on the role of parents in the mechanisms that make possible and even reinforce the sexual exploitation of women in Europe.